Space Weather Research Towards Applications in Europe - Lilensten, Jean.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
This book shows the state of the art in Europe on a very new discipline, Space Weather. This discipline lies at the edge between science and industry. This book reflects such a position, with theoretic papers and applicative papers as well. It is divided into 5 chapters. Each chapter starts with a short introduction, which shows the coherence of a given domain. Then, 4 to 5 contributions written by the best specialists in Europe give detailed hints of a hot topic in space weather. From the reading of this book, it becomes evident that space weather is a living discipline, full of promises and already full of amazing realizations. The strength of Europe is clear through the book, but it is also clear that this discipline is world wide.
The Solar Weather/Solar Activity Monitoring and Forecast -- Using CME Observations for Geomagnetic Storm Forecasting -- Solar Activity Monitoring -- Modeling of Solar Energetic Particles in Interplanetary Space -- Simulating CME Initiation and Evolution: State-of-the-art -- Signatures of the Ancient Sun Constraining the Early Emergence of Life on Earth -- The Sun's Interaction with the Earth's Thermosphere and Climate System -- Solar Variability and Climate -- Influence of Solar Activity Cycles on Earth's Climate -- Unravelling Signs of Global Change in the Ionosphere -- Thermosphere Density Model Calibration -- Numerical Space Weather Prediction: Can Meteorologists Forecast the Way Ahead? -- Ionosphere/Positioning and Telecommunications -- Space Weather Influence on Satellite-based Navigation and Precise Positioning -- New improvements in HF Ionospheric Communication and Direction Finding Systems -- Short-Term fo F2 Forecast: Present Day State of Art -- Manifestation of Strong Geomagnetic Storms in the Ionosphere above Europe -- Effects of Scintillations in GNSS Operation -- Radiation Environment of the Earth-Spacecraft and Aircraft Environment -- Complementarity of Measurements and Models in Reproducing Earth's Radiation Belt Dynamics -- Radiation Effects on Spacecraft and Countermeasures, Selected Cases -- Aircraft Crew Radiation Exposure in Aviation Altitudes During Quiet and Solar Storm Periods -- The Magnetic Environment - GIC and other Ground Effects -- Geomagnetic Indices in Solar-Terrestrial Physics and Space Weather -- The Value of Real-time Geomagnetic Reference Data to the Oil and Gas Industry -- Spatiotemporal Characteristics of the Ground Electromagnetic Field Fluctuations in the Auroral Region and Implications on the Predictability of Geomagnetically Induced Currents -- Finnish Experiences with Grid Effects of GIC's.
Keywords: PHYSICS; METEOROLOGY; ASTRONOMY; ENVIRONMENTAL SCIENCES; ENVIRONMENTAL PROTECTION; PHYSICS; ASTRONOMY, ASTROPHYSICS AND COSMOLOGY; METEOROLOGY/CLIMATOLOGY.; ENVIRONMENT, GENERAL; EFFECTS OF RADIATION/RADIATION PROTECTION; GEOSCIENCES, GENERAL